Unusual Case of Resistance to Amphotericin B in Visceral Leishmaniasis in a Region in India Where Leishmaniasis Is Not Endemic - Srivastava, Pankaj (American Society for Microbiology, 2011)
The case of a patient with visceral leishmaniasis showing inadequate response to amphotericin B from a region where leishmaniasis is not endemic is reported, with the Leishmania donovani isolate showing increased tolerance to amphotericin B in vivo. Four single nucleotide polymorphisms (SNPs) detected in the cysteine proteinase B gene resulted in changes to the deduced amino acid sequence: valine→alanine and arginine→leucine. Overexpression and underexpression of proteins were observed in the 65- to 80-kDa range and at 20 kDa, respectively.